A Characterization of the Impact Toughness of Hot-rolled HSLA Steel - Hamryszczak, Tomasz; Śleboda, Tomasz; Lypchanskyi, Oleksandr; Pańcikiewicz, Krzysztof (Journal of Casting & Materials Engineering, 2024)
Due to the wide use of HSLA steels in difficult conditions, e.g. at low temperatures, it is extremely important to test the impact strength of these steels. This is equally important because most of those structures are made by welding these steels, and the welding process itself has a significant impact on the properties of joints and welding zones. In this work, the authors analyzed two selected representative HSLA steels rolled in the Krakow branch of ArcelorMittal Poland S.A. – the only place in Poland where HSLA steels in the form of hot-rolled strips can be produced on an industrial scale. Impact tests were performed in accordance with technical acceptance standards, and then the fracture surfaces after impact tests were characterized using light and scanning microscopy. In the next part of the work, a set of previously gathered data were analyzed to determine the influence of thermomechanical rolling process parameters on the level of impact strength and the influence of chemical composition on it.